The use of critical thinking technology at the Russian language classes - Dzhumabekova, A.A.; Ermekova, A.B. (KSU Publ., 2020)
This article is devoted to the problem of forming students ' critical thinking. According to the authors, this problem is often left without proper attention from the teacher. The article considers the possibility of introducing and using critical thinking technology in the educational process, and analyzes the main approaches to this definition. Special emphasis is placed on the techniques and methods that must be used at different stages of learning the Russian language, as well as specific examples of the use of these methods. The necessity of generalizing conceptual research and deepening the theoretical model of critical thinking is stated. Special attention is paid to the structure of the lesson and the techniques of this technology. The article analyzes the concept of critical thinking as a factor of professional competence, the main principles and technological phases of its development, as well as four main variants of the organization of critical thinking in students.
Орыс тілі сабағында сыни тұрғыдан ойлау технологиясын қолдану
Использование технологии критического мышления на занятиях русского языка
Keywords: critical thinking; education; problem; development; rational thinking; teacher; student